2003
DOI: 10.1111/j.0105-1873.2003.0217.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical tacrolimus 0.1% ointment (Protopic®) reverses nickel contact dermatitis elicited by allergen challenge to a similar degree to mometasone furoate 0.1% with greater suppression of late erythema

Abstract: The aim of this study was to evaluate the ability of topical tacrolimus 0.1% under occlusion for 48 h to suppress nickel-elicited allergic contact dermatitis in a randomized, petrolatum- and mometasone furoate 0.1% ointment-controlled double-blind, intra-individual study which included 28 women volunteers. 3 closed patch tests (Finn Chambers on Scanpor, Epitest Ltd Oy, Tuusula, Finland) containing 0.1 ml of 5% nickel sulfate in petrolatum were applied on day 0. After removal on day 2, the study compounds were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 11 publications
1
22
0
5
Order By: Relevance
“…It has also been demonstrated to inhibit T‐lymphocyte activation and dermal skin Langerhans’ cells, but with a good safety profile and without the side‐effects of corticosteroids 7,8 . In contrast to corticosteroids, tacrolimus effectively controls erythema and oedema, not as a result of vasoconstriction, but perhaps by a direct anti‐inflammatory effect 9 …”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated to inhibit T‐lymphocyte activation and dermal skin Langerhans’ cells, but with a good safety profile and without the side‐effects of corticosteroids 7,8 . In contrast to corticosteroids, tacrolimus effectively controls erythema and oedema, not as a result of vasoconstriction, but perhaps by a direct anti‐inflammatory effect 9 …”
Section: Introductionmentioning
confidence: 99%
“…However, Saripalli et al 49 induced nickel ACD in patients and found that tacrolimus was significantly more effective than vehicle. Alomar et al 50 corroborated this finding. Similarly, pimecrolimus at 0.2% and 0.6% formulations has successfully treated nickel-induced ACD 51…”
Section: Discussionmentioning
confidence: 75%
“…The TCIs may offer a steroid-sparing treatment for some forms of CD. [106][107][108][109][110][111] Evaluation of tacrolimus ointment has shown a treatment benefit in nickel allergy, 107,109 protein contact dermatitis, 106 and eyeglass frame dermatitis. 107 Similarly, pimecrolimus has exhibited efficacy in the treatment of nickel 110 and chronic hand dermatitis.…”
Section: Contact Dermatoses In Adolescentsmentioning
confidence: 99%